Effects of a physical activity behavior change intervention on inflammation and related health outcomes in breast cancer survivors: pilot randomized trial - Rogers, Laura Q. (2012)
BACKGROUND: Physical activity may provide benefits for breast cancer survivors in part by reducing systemic inflammation. Physical activity behavior change studies are a type of implementation research in which exercise efficacy information is translated into a “real world” setting, allowing determination of whether physical activity changes are sufficient to improve health outcomes. We hypothesized that breast cancer survivors (BCS) who undertook a physical activity behavior change intervention would have less systemic inflammation and improved cardiorespiratory fitness, muscle strength, body composition, fatigue, and sleep as compared with BCS receiving usual care. The goal of this pilot study was to determine the magnitude and direction of intervention effect sizes for inflammatory related serum markers and relevant health outcomes. METHODS: This randomized controlled trial enrolled 28 Stage I, II, or IIIA BCS who were post-primary treatment and were not regular exercisers. These women were assigned to either a 3-month physical activity behavior change intervention group (ING) or usual care group (UCG). Intervention included supervised aerobic (150 weekly minutes, moderate-intensity) and resistance (two sessions per week) exercise that gradually tapered to home-based exercise. At baseline and after 3 months, health outcomes and serum concentrations of interleukin (IL)-1 beta, IL-6, IL-8, IL-10, tumor necrosis factor (TNF)-alpha, leptin, and adiponectin were measured. RESULTS: Cardiorespiratory fitness significantly improved in the ING versus UCG (between group difference=3.8 ml/kg/min; d=1.1; P=0.015). Self-reported sleep latency was significantly reduced in the ING versus UCG (between group difference=−0.5; d=−1.2; P=0.02) as was serum leptin (between group difference=−9.0 ng/ml; d=−1.0; P=0.031). Small to medium non-significant negative effect sizes were noted for IL-10 and TNF-alpha and ratios of IL-6:IL-10, IL-8:IL10, and TNF-alpha:IL-10, with non-significant positive effect sizes noted for IL-6 and high molecular weight adiponectin. CONCLUSIONS: Physical activity behavior change interventions in BCS can achieve large effect size changes for several health outcomes. Although effect sizes for inflammatory markers were often small and not significant, changes were in the hypothesized direction for all except IL-6 and IL-10. These preliminary data support larger trials that would more fully examine potential inflammatory changes that accompany physical activity behavior change interventions.